Erosion of state power, corruption control, and political stability - Weijia Li; Gérard Roland; Yang Xie (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
How do corruption and the state apparatus interact, and how are they connected to the political and economic dimensions of state capacity? Motivated by historians' analysis of powerful empires, we build a model that emphasizes the corrosive effect of corruption on state power. Under general assumptions about fat-tailed risk, we show that, if fiscal capacity is strong, then the optimal response for the head of the state apparatus will be an endogenous lexicographic rule whereby local corruption is maintained at such a level that no erosion of state power is tolerated. Comparative statics shows the impacts of additional risk of crisis on corruption tolerance as well as the complementarity between personalistic rule and corruption. Implications of corruption at the head of the state apparatus are also analyzed. If fiscal capacity is not sufficiently strong, however, the state will have to over-tolerate corruption to retain its affiliates, risking its control in crises. Our model predicts that the correlation between state's political stability and corruption is non-monotonic across different levels of fiscal capacity, and this prediction is robustly consistent with recent cross-country panel-data.
URN:NBN:fi:bof-202002262003
Keywords: D73; H12; D02; 330; Corruption; state apparatus; state capacity; crisis; erosion of stateauthority; bureaucracy